Integrated Traditional Chinese and western medicine nursing of a patient with COVID-19 complicated with chronic cough (1例新型冠状病毒感染合并慢性咳嗽患者的中西医结合护理体会) - YANG Xiaoyu (杨肖雨); CAO Hongjing (曹红京); LI Ning (李宁); LI Yueru (李月茹); LI Jing (李静); ZHENG Xinnan (郑鑫楠) (中西医结合护理)
This article summarized integrated Traditional Chinese and western medicine nursing interventions for a patient with COVID-19 complicated with chronic cough. Based on the nursing risk assessment and Traditional Chinese Medicine syndrome differentiation, a comprehensive nursing plan consisted of prone position ventilation, health education, emotion regulation and other interventions were carried out. In addition, Traditional Chinese Medicine nursing techniques such as dressing aromatherapy, Chinese herbal medicine ointment rubbing, acupoint application, auricular acupoint pressing and five-tone music therapy were carried out to relieve the negative emotion and cough symptoms, and improve patient’s quality of life. (本文总结1例新型冠状病毒感染合并慢性咳嗽患者的中西医结合护理体会。基于护理评估和中医辨证, 在俯卧位通气、健康宣教、情志护理等常规护理干预基础上, 开展衣冠疗法、中药膏摩、穴位贴敷、耳穴压丸、五音疗法等中医适宜技术, 有效改善患者负性情绪, 缓解咳嗽症状, 提高生活质量。)